Effects of viscous dissipation in flow-influenced tube hydroforming. (4th February 2008) - Dal Bo, P.; Geiger, M.
In tube hydroforming, the forming results can usually be improved if axial feeding at one or both tube ends is enabled. For very long parts, however, owing to the high-friction forces acting between the tube and die at high pressure, no material flow to the forming area occurs. With the flow of a highly viscous fluid on the tube's surfaces, external pressure and tangential axial forces are generated, which reduce the normal contact force between the tube and die and help the sliding of the tube in the forming zone. In this paper, the behaviour of a flowing Newtonian highly viscous fluid was analysed. 2D and 3D coupled thermomechanical FE analyses were done to study the effects of viscous dissipation and conductive and convective heat transfers between fluid and tool. The results of the simulation were validated with temperature measurements during the experiments on the hydroforming tool.